2002
DOI: 10.1046/j.1365-3180.2002.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved management of Avena ludoviciana and Phalaris paradoxa with more densely sown wheat and less herbicide

Abstract: Summary The effectiveness of crop competition for better weed control and reducing herbicide rates was determined forAvena ludoviciana and Phalaris paradoxa. Four experiments, previously broadcast with seeds of the two weeds in separate plots, were sown with three wheat densities, and emerged weeds were treated with four herbicide doses (0–100% of recommended rate). The measured crop and weed traits were first analysed across experiments for treatment effects. Grain yield and weed seed production data were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 26 publications
5
45
0
2
Order By: Relevance
“…Estudos relacionados sugerem, também, que é possível aumentar o retorno econômico com o uso de doses reduzidas de herbicidas, desde que aplicadas em conjunto com medidas de manejo integrado de plantas daninhas (Boström et al, 2000;Popp et al, 2000). Resultados similares foram relatados por Walker et al (2002), porém, neste caso, a redução da dose herbicida dependeu da densidade e do estádio das plantas daninhas.…”
Section: Introductionunclassified
“…Estudos relacionados sugerem, também, que é possível aumentar o retorno econômico com o uso de doses reduzidas de herbicidas, desde que aplicadas em conjunto com medidas de manejo integrado de plantas daninhas (Boström et al, 2000;Popp et al, 2000). Resultados similares foram relatados por Walker et al (2002), porém, neste caso, a redução da dose herbicida dependeu da densidade e do estádio das plantas daninhas.…”
Section: Introductionunclassified
“…Using management practices that increases crop competitiveness may reduce the negative effects associated with the use of low herbicide rates. Different studies have shown that control of sterile oat (Avena sterilis) and paradoxa grass (Phalaris paradoxa) populations can be improved by using competitive crop cultivars and high seeding rates (Walker et al, 2002;FernandezQuintanilla et al, 2006). Integrating these practices with the use of low herbicide rates may provide an agronomically viable and environmentally friendly solution for short-spiked canary grass control under semi-arid conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Walker et al (2001Walker et al ( , 2002 showed that control of wild oats and paradoxa grass was improved substantially with increased competition from winter cereals, and growers in the intensive cropping region of Darling Downs in Southern Queensland considered increasing crop density as an important weed control practice (Streit 1996). In contrast, only a few growers sowed their dryland cotton and rotational crops at higher seeding rates, and this option needs to be explored for summer crops in this environment, and more widely adopted for winter crops of the rotations.…”
Section: Discussionmentioning
confidence: 99%